The lantern's dance : a novel of suspense featuring Mary Russell and Sherlock Holmes - King, Laurie R. (King, Laurie R. Mary Russell novel, 2024)
"Mary Russell and Sherlock Holmes, hoping for a respite in the French countryside, are instead caught up in a case that turns both bewildering and intensely personal. After their recent adventures in Transylvania, Russell and Holmes look forward to spending time with Holmes' son, the famous artist Damian Adler, and his family. But when they arrive at Damian's house, they discover that the Adlers have fled from a mysterious threat. Holmes rushes after Damian while Russell, slowed down by a recent injury, stays behind to search the empty house. In Damian's studio, she discovers four crates packed with memorabilia related to Holmes' grand-uncle, the artist Horace Vernet. It's an odd mix of treasures and clutter, including a tarnished silver lamp with a rotating shade: an antique yet sophisticated form of zoetrope, fitted with strips of paper whose images dance with the lantern's spin. In the same crate is an old journal written in a nearly impenetrable code. Intrigued, Russell sets about deciphering the intricate cryptograph, slowly realizing that each entry is built around an image--the first of which is a child, bundled into a carriage by an abductor, watching her mother recede from view. Russell is troubled, then entranced, but each entry she decodes brings more questions. Who is the young woman who created this elaborate puzzle? What does she have to do with Damian, or the Vernets--or the threat hovering over the house? The secrets of the past appear to be reaching into the present. And it seems increasingly urgent that Russell figure out how the journal and lantern are related to Damian--and possibly to Sherlock Holmes himself. Could there be things about his own history that even the master detective does not perceive?"--